Competition performance and basal nocturnal catecholamine excretion in cross-country skiers - Knoepfli, B.; Calvert, R.; Bar-Or, O.; Villiger, B.; von Duvillard, S. P. (Medicine & Science in Sports & Exercise, 2001)
Objective techniques to determine whether an athlete is optimally prepared for a competition are virtually nonexistent. Preparedness for sports competition is commonly judged through the experience of the athletes and their coaches. Evidence from overtraining studies suggests that catecholamine (Cat) excretion rates may correlate with performance in athletes. PURPOSE: We therefore attempted to determine whether a relationship existed between performances of world-class cross-country skiers and basal nocturnal Cat excretion (BNCE). METHOD: During the Cross-Country Skiing World Championships, we determined BNCE in nine cross-country skiers of the Swiss national team by measuring free Cat concentration (dopamine = D, norepinephrine = NE, epinephrine = E) in morning urine samples, using high performance liquid chromatography. Expert judgments of competition performance (ECP) were assessed by two experienced professional coaches of the national team by using an 11-step scale. RESULTS: The BNCE correlated significantly with ECP in cross-country skiers (r2 = 0.84 and P < for NE; r2 = 0.86 and P < 0.001 for D). Athletes who had their best absolute competition results (ACR) showed the highest NE and D concentrations. CONCLUSION: These data suggest that competitive cross-country skiers with higher D and NE excretion may reach better competition levels compared with those with lower levels. Measures of BNCE provide objective information about competition performance, which may benefit athletes in their precompetition preparation.